A mesoscopic model for simulating the physisorption process in nanopores. (23rd November 2022) - Dou, Shaojun; Hao, Liang; Liu, Hong
Highlights: The mesoscopic lattice Boltzmann pseudopotential model is used to simulate the phase behavior of the confined fluids and the physisorption process in nanopores. The model accurately captured the essential characteristics of different types of physisorption isotherms, and revealed the underlying mechanisms of adsorption hysteresis. The potential and advantages of the pseudopotential model for simulating the physisorption process in nano-porous media are discussed. Abstract: In this study, we applied the lattice Boltzmann pseudopotential model to systematically simulate the phase behavior of the confined fluids and the physisorption process in nanopores. The simulation results indicated that the pseudopotential model could well describe the thermodynamic and phase behaviors of the confined fluids on the molecular level. By performing numerical adsorption experiments in nanopores, the model accurately captured the essential characteristics of types I and IV physisorption isotherms in micropores and mesopores, respectively, and revealed the underlying mechanisms of adsorption hysteresis induced by adsorption metastability and network effects. The present work shows the potential and advantages of the pseudopotential model to simulate the physisorption process in nano-porous media.